Low Serum Vitamin B12 in AlzheimerÃ»s Patients as Detected by a Solid Phase Radioimmunoassay - Areechun Sotthibundhu; Doungjai Buntup; Channarong Sanghirun; Korbkit Cherdchu; Cheeraratana Cheeramakara; Sirintorn Chansirikarnjan; Ekapot Nimkulrat; Chesda Udommongkol; Wanna Wongmek; Wipawan Thangnipon (Siriraj Medical Journal, 2008)
Objective: To determine the relationship between serum levels of vitamin B12 and folate in AD and other types of dementia in Thai patients. Methods: One hundred and eleven Thai subjects were classified into 3 groups: 32 AD patients, 43 non-AD dementia patients and 36 age-matched controls. Serum concentrations of vitamin B12 and folate were measured using a solid phase radioimmunoassay. Results: Serum vitamin B12 levels were found to be significantly lower in AD and non-AD dementia patients than in age-matched controls. There is a significant relationship between Mini-Mental State Examination score and vitamin B12 level in AD and non-AD dementia groups. However, there is no significant difference in serum folate in AD and non-AD dementia groups when compared to age-matched controls. Conclusion: These findings suggest the need for vitamin B12 supplementation in AD and non-AD dementia patients.